Problematika Advokasi Kebijakan Publik Oleh Kelompok Masyarakat Sipil Di Kota Pontianak : (Studi Advokasi Kebijakan Publik Tentang Toleransi Di Kota Pontianak) - Dawi, Klara; Wagner, Ivan; Yuliastiani, Anita; Loin, Raymundus; Pratama, Erwin Aditya (Diktum: Jurnal Ilmu Hukum, 2021)
One of the civil society groups currently advocating for public policy in Pontianak City is the Pontianak Bhinneka Network (PBN). As for public policy advocacy by the Pontianak Bhinneka Network regarding tolerance, it is interesting to examine the problems. The limitation scope of the problem is about problems of public policy advocacy by civil society groups. The PBN has made a fairly systematic and structured effort in advocating and encouraging policies on tolerance in Pontianak City. However, there are still problems faced by PBN in conducting policy advocacy covering internal and external aspects. From the internal aspect, it focuses on organizational capacity and relates to autonomy, especially related to funding and sustainability. Problems from the external aspect regarding relations with state actors and other actors, and managing public issues related to policy issues that are being pushed. The two external problems are interrelated, and related to sub-systems, namely legal substance, legal structure, and legal culture.